Tomato Yellow Leaf Curl Virus-Is Causes a Novel Disease of Common Bean and Severe Epidemics in Tomato in Spain - Navas-Castillo, Jesús (Plant disease, 1999)
Field surveys were conducted in the autumn of 1997 in the main tomato (Lycopersicon esculentum)-growing regions of southern Spain following a severe tomato yellow leaf curl epidemic in tomato. Tomato yellow leaf curl virus (TYLCV)-Is was found to have spread to all regions and to coexist with TYLCV-Sr, which has been present since 1992. TYLCV-Is was also shown to be the causal agent of bean leaf crumple, a novel disease that has caused severe economic losses in fresh-market common bean (Phaseolus vulgaris) crops of southern Spain since September 1997. The disease was reproduced by infecting beans with cloned TYLCV-Is obtained from infected tomato plants collected in Almería. This is the first report of bean leaf crumple disease and the first report of a geminivirus in bean from Spain